2019
DOI: 10.1055/a-0860-1694
|View full text |Cite
|
Sign up to set email alerts
|

Psychologische Aspekte von Hochintensivem Intervalltraining (HIIT) in der Therapie: Eine Übersicht der Literatur

Abstract: ZusammenfassungDer Beitrag gibt eine Literaturübersicht zu psychologischen Aspekten von Hochintensivem Intervalltraining (HIIT) in der Therapie anhand von 13 Studien mit insgesamt 1204 Patienten. Die bisherige Forschung analysiert überwiegend Lebensqualität, Depression, Angst und Erschöpfung. Hinsichtlich positiver Effekte sind die Ergebnisse inkonsistent. Negative psychische Effekte von HIIT konnten nicht nachgewiesen werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Based on a literature review, Kleinert & Bassek (2019) concluded that the positive effects of HIIT on the quality of life, depression, anxiety and fatigue are inconsistent. However, they did not nd proof of the negative psychological effects of HIIT 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on a literature review, Kleinert & Bassek (2019) concluded that the positive effects of HIIT on the quality of life, depression, anxiety and fatigue are inconsistent. However, they did not nd proof of the negative psychological effects of HIIT 42 .…”
Section: Introductionmentioning
confidence: 99%